Conserved and divergent expression patterns of markers of axial development in eutherian mammals. Issue 1 (28th October 2015) - Yoshida, Michio; Kajikawa, Eriko; Kurokawa, Daisuke; Tokunaga, Tomoyuki; Onishi, Akira; Yonemura, Shigenobu; Kobayashi, Kensaku; Kiyonari, Hiroshi; Aizawa, Shinichi
Abstract : Background : Mouse embryos are cup shaped, but most nonrodent eutherian embryos are disk shaped. Extraembryonic ectoderm (ExEc), which may have essential roles in anterior–posterior (A‐P) axis formation in mouse embryos, does not develop in many eutherian embryos. To assess A‐P axis formation in eutherians, comparative analyses were made on rabbit, porcine, and Suncus embryos.Results : All embryos examined expressed Nodal initially throughout epiblast and visceral endoderm; its expression became restricted to the posterior region before gastrulation. Anterior visceral endoderm (AVE) genes were expressed in Otx2 ‐positive visceral endoderm, with Dkk1 expression being most anterior. The mouse pattern of AVE formation was conserved in rabbit embryos, but had diverged in porcine and Suncus embryos. No structure that was molecularly equivalent to Bmp ‐positive ExEc, existed in rabbit or pig embryos. In Suncus embryos, A‐P axis was determined at prehatching stage, and these embryos attached to uterine wall at future posterior side.Conclusions : Nodal, but not Bmp, functions in epiblast and visceral endoderm development may be conserved in eutherians. AVE functions may also be conserved, but the pattern of its formation has diverged among eutherians. Roles of BMP and NODAL gradients in AVE formation seem to have been established in a subset of rodents. Developmental Dynamics 245:67–86, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Anterior‐posterior axis formation was examined in disk‐shaped eutherian embryos. Anterior visceral endoderm (AVE) functions may be conserved in eutherians. The pattern of AVE formation may be conserved in Glires but diverged in Laurasiatheria. Extraembryonic ectoderm functions seem to have evolved in a subset of rodents. Nodal functions in prestreak development may be conserved among eutherians.